Kajian Sistematis Agen dan Faktor Yang Berkontribusi Terhadap Kejadian Luar Biasa (KLB) Keracunan Pangan Di Indonesia Tahun 2000 – 2015 (Berita Kedokteran Masyarakat (BKM), 2018)
Background: Foodborne outbreak report in Indonesia increase recently. It was showed by case fatality rate 0.16% in 2011 become 1.3% in 2015. There is no foodborne outbreak baseline data including agent that mostly caused food contamination and specific situation that contributed on foodborne. Accurate and comprehensive epidemiology data need to early warning system, outbreak response and control. Purpose of study is to understand burden of foodborne outbreak in Indonesia during 2000 -2015.Methods: Systematic review conducted based on publish and unpublished (grey literature) data during 2000 -2015. Publish data from search engine such as Google scholar, open access, repository online university in Indonesia. Grey literature collected from investigation report from selected university (UGM, UI and UNAIR), Ministry of Health, Food and Drug Administration (BPOM) Indonesia. 2 reviewer will select and extract relevant data.Outcome: During 2000 – 2015 there was 1.176 foodborne outbreak with West Java Province as the highest event with 61.119 foodborne cases (AR: 8.5%) and 291 deaths (CFR: 0.4%). Women have more risk on foodborne with proportion 58.3%. Daily meal (36.6%) and special celebration (29.7%) as more risk activities with house (48.9%) and school (13.7%) as highest risk area for foodborne outbreak. Homemade food (46.9%) and catering food (18.9%) as highest causes of cases with pathogen bacterial as frequent agent (74.9%) such as E.coli. The most contributing factor was inadequate cooking and storage at inappropriate temperature.Conclusion: High risk population of foodborne outbreak was women with pathogen bacterial as the highest agent. The most contributing factor was pathogen resistance and growth. It need to increase monitoring and food-handler as food safety standard.